Anion Exchange Membranes for Fuel Cells: State‐of‐the‐Art and Perspectives. Issue 28 (2nd June 2022) - Chen, Huanhuan; Tao, Ran; Bang, Ki‐Taek; Shao, Minhua; Kim, Yoonseob
Abstract: Fuel cell technology is a clean way of generating energy and should enable carbon neutrality. However, although traditional proton exchange membrane fuel cells (PEMFCs) have made a commercial impact, their high cost hinders their wider adoption. Fuel cells that use anion exchange membranes (AEMs) are a promising alternative to PEMFCs, as they can achieve the same performance at a lower cost. In this Perspective, recent trends in the fabrication of polymer‐based high‐performance AEMs are highlighted and future directions are identified. Since ensuring the durability of polymers in strong alkaline conditions is the most critical issue in the development of AEM fuel cells, strategies for the formation of polymers with chemical stability, mechanical stability, and ionic conductivity are primarily focused on. Successes in polymer design are expected to inaugurate the next generation of AEMs and trigger a fresh wave of innovation, leading to the development of long‐lasting fuel cells that reduce carbon emissions and facilitate sustainable development. Abstract : This perspective presents the current state‐of‐the‐art in anion exchange membranes (AEMs) for fuel cells, including the design principles and synthetic strategies. A summary of challenges encountered for current ether‐free AEMs, and a discussion of the opportunities for developing next‐generation AEMs is presented. Ether‐free polyarylene‐ and polyethylene‐based AEMs with further improved processibility and stability have great potential and will be the focus of the field.